2019
DOI: 10.5530/ijopp.12.3.40
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Beliefs and Attitudes towards Herbal Medicine – A Community-based Survey from a Central Region of Saudi Arabia

Abstract: Background and Objectives: Herbal products are widely used in many countries in various forms including roots, leaves, barks seeds and so many, for inhibiting and treating Number of minor and major disorders. The purpose of this study was to evaluate the prevalence of self-medication with complementary and alternative medicine (CAM) in capital of Saudi Arabia (SA). Methods: A cross-sectional, descriptive online survey was conducted among general public from February to April 2018 using Google Forms. The survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…In Saudi Arabia, 75.6% of the general public in Riyadh reported using herbal medicines [ 17 ]. This high utilization rate of herbal medicines among the general public was attributable to the common belief that herbal medicines are generally safe [ 17 , 18 , 19 ]. Additionally, it has been reported in a study, which surveyed a sample of herbal medicine consumers in Saudi Arabia, that herbal medicines are generally harmless and safe [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Saudi Arabia, 75.6% of the general public in Riyadh reported using herbal medicines [ 17 ]. This high utilization rate of herbal medicines among the general public was attributable to the common belief that herbal medicines are generally safe [ 17 , 18 , 19 ]. Additionally, it has been reported in a study, which surveyed a sample of herbal medicine consumers in Saudi Arabia, that herbal medicines are generally harmless and safe [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Medicinal herbs, such as myrrh and ginseng, were reported to be used by 37% of the surveyed adolescents, and females reported a higher rate of utilization and more favorable views of medicinal herbs in comparison to their male counterparts [ 20 ]. Furthermore, ginger and cinnamon were utilized most frequently among females according to a community-based survey in the central region in Saudi Arabia [ 19 ]. Additionally, participants reported that they used CAM for joint pain and chronic disease states such as diabetes, hypertension, and dyslipidemia [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, increased administration of raw products has the potential risk for adverse drug–drug interactions and significant pharmacodynamics and pharmacokinetics with other conventional drugs, reducing the efficacies of the latter medicines [ 10 ]. For instance, in Saudi Arabia, the utilization of high levels of natural raw products, such as honey, black cumin, dietary supplements, myrrh, ginseng, cinnamon, and ginger, across the different regions within the country occurred before the COVID 19 pandemic as shown by many studies [ 11 , 12 , 13 ]. This is probably attributable to the common attitude and satisfaction towards these products based on many aspects of local lifestyles and beliefs [ 12 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in Saudi Arabia, the utilization of high levels of natural raw products, such as honey, black cumin, dietary supplements, myrrh, ginseng, cinnamon, and ginger, across the different regions within the country occurred before the COVID 19 pandemic as shown by many studies [ 11 , 12 , 13 ]. This is probably attributable to the common attitude and satisfaction towards these products based on many aspects of local lifestyles and beliefs [ 12 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%